IMPLEMENTASI WEBSITE UNTUK MENINGKATKAN OMSET PENJUALAN BATIK BERKAH LESTARI - Radjaban Radjaban; Septi Riana Dewi; Rianto Rianto (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2021)
Marketing is one of the determinant factors on business success, even though there are still many negligent companies and still use conventional systems so that their sales turnover is low. The COVID-19 pandemic also creates problems on sales turnover. Micro, Small, and Medium Enterprises of Batik Berkah Lestari Imogiri are among those affected by the pandemic. This is related to the conventional marketing system that has been implemented up to this time. In addition, government policies related to pandemics also limit life activities. People are no longer free to visit shopping centers, so they need to make transaction media without leaving their homes. The development of internet technology has presented a medium called a website. Its flexibility, convenience, and simplicity make webiste to be widely used. Moreover,  the existence of website will be used for Batik Berkah Lestari in marketing its products during the pandemic. This study aims to implement the website as an online transaction medium for Batik Berkah Letasri. By utilizing the website as a medium for electronic transaction, the market reach will be even wider so that transaction opportunities at Batik Berkah Lestari will be even greater.